Comparison of Administrative Models in Indonesia: Centralization VS Decentralization Approaches (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
This research explores the comparison of administrative models in Indonesia, specifically analyzing centralization and decentralization approaches. By employing policy analysis and empirical data, the study evaluates the strengths and weaknesses of each model concerning efficiency, accountability, and public engagement. The findings indicate that while decentralization can significantly enhance community participation and responsiveness to local needs, it also introduces risks of inequality and disparities in resource allocation among regions. Conversely, centralization offers a streamlined decision-making process that can lead to uniformity in policy implementation but may hinder local adaptability and citizen involvement. This study presents a series of recommendations aimed at designing a more balanced administrative model that integrates the benefits of both centralization and decentralization, ultimately promoting equitable governance and improved public service delivery across Indonesia.